2015
DOI: 10.1007/s12646-015-0307-9
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Trust and Hope among Women: A Qualitative Study

Abstract: The study is about 'trust and hope', a positive approach adopted by women to overcome the trauma in their lives successfully. It aims to understand what it takes to counter depressing moments and develop positivity in life. Employing the grounded theory approach an empirical investigation into the lives of women revealed (a) the causal conditions that underlie the development of trust and hope; (b) identified the phenomena, 'trust and hope', that develop from causal conditions; (c) context and intervening cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…A brief review of 21 scholarly publications using the subject terms "hope" and "grounded theory" showed that the majority (17) highlighted interpersonal aspects, including: ways to foster parental hope (Bally et al 2014), inspiring psychotherapy client hopes (Chamodraka et al 2017), promoting hope in the bereaved (Cutcliffe 2004), trust and hope in trauma survivors (Srivastava 2015), collective workplace hope (Barron 2015), and the promotion of hope in vulnerable or HIV affected youth (Thampanichawat 2008). Nevertheless, any grounded inquiry of hope must be tempered by Bloch's 1995) central insight that a full understanding of hope must include the here and now as well as the "not-yet" manifested in time or space, awareness or belief.…”
Section: Grounded Theorymentioning
confidence: 99%
“…A brief review of 21 scholarly publications using the subject terms "hope" and "grounded theory" showed that the majority (17) highlighted interpersonal aspects, including: ways to foster parental hope (Bally et al 2014), inspiring psychotherapy client hopes (Chamodraka et al 2017), promoting hope in the bereaved (Cutcliffe 2004), trust and hope in trauma survivors (Srivastava 2015), collective workplace hope (Barron 2015), and the promotion of hope in vulnerable or HIV affected youth (Thampanichawat 2008). Nevertheless, any grounded inquiry of hope must be tempered by Bloch's 1995) central insight that a full understanding of hope must include the here and now as well as the "not-yet" manifested in time or space, awareness or belief.…”
Section: Grounded Theorymentioning
confidence: 99%
“…Persons often attempt to overcome a traumatic event in their lives by actively searching for and developing coping mechanisms (Engebretsen & Bjorbaekmo, 2020;Srivastava, 2015). Coping mechanisms may be problemfocused or emotion-focused (Lazarus & Folkman, 1984), and the former type is generally consistent with survivors of chronic disease and is associated with a better quality of life (Black et al, 2020;Shakeri et al, 2015;Srivastava, 2015). Problem-focused coping refers to a positive reframing and active reappraisal of behavior to gain control and resolve a crisis (Mehrabi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is directly associated with a transformation of the self to fit with the characteristics of the traumatic life experience such as a disease state and subtly different to the self previously presented to others in day-to-day life. Positive meaning-making can lead to self-growth (Ching et al, 2012; Connerty & Knott, 2013; Park et al, 2009) and PTG (Connerty & Knott, 2013; Srivastava, 2015) and is similar to PTG in that they both lead to a higher sense of awareness and acceptance as well as promoting a more insightful and reflective state that may ultimately instigate an epiphanic experience (Denzin, 2001). Epiphany is a moment of profound realization—a turning point in one’s life that is unpredictable and uncontrollable yet inspires major life changes (McDonald, 2007; Mulkins & Verhoef, 2004).…”
Section: Introductionmentioning
confidence: 99%